The conflict of conscience on judge Enrique Lopez Albujar - Lira Pinto, Jorge (2012)
A judgment issued in Peru in 1917 related to an act of adultery with singulars characteristics: the judge recognizes that the ruling stipulates to criminally punishthe adultery, however he does not agree with the mandate for the reasons set out on his judgment, and absolve the defendants. The author of that judicial arder is nothing less than Enrique Lopez Albujar, notable Peruvian writer. There is not involved lack of awareness nor banal motivations. It is simply a conflict of conscience